Liking or disliking current home: Listening to children who reside in state-run children's homes and foster homes in Malaysia - Chan, Cheong Chong (2012)
Residential child care is widely known in Malaysia, but this is not the case for foster care.Studies of foster home are limited and not popular as compared to studies of children's home.This paper presents children's immediate responses o f like or dislike about the trio mentioned substitute homes. 25 foster children and 37 children in children's homes were interviewed.All participants are Malay and aged 10 to 15 year-old.Findings show that more foster children liked their foster homes as compared with their counterparts in children's homes.Outing, foster mother, and comfortable living setting were some of the reasons given by the foster children.Conversely, children in children's homes disliked their homes mainly because o f the pooling system, regulations and staffs attitudes. Overall, foster home appears to be a better received placement than children's home.Nevertheless, children's narrations imply that the main attributes to children's views about their homes are the quality of reciprocal interaction and level of personal acceptance.